Autoconceito, autoeficácia e parentalidade : crianças com deficiência física, com desenvolvimento típico e seus familiares - Oliveira, Alyne Kalyane Câmara de (2016)
For the group of children with physical disabilities, beyond the motor impairments their own health condition and contextual factors, at how the child self-assesses, as the own self-concept and own self-efficacy, may lead to repercussions in learning, behavior and the child feature. Among the contextual factors, points out the influence of family caregivers in the development of self-concept and self-efficacy of their children, from how guide their children's behavior in daily life, also called as practices and parenting styles. Considering the importance of selfconcept and self-efficacy in the child development process in general and, specifically, the physically disabled children, to use their skills in daily activities and as a motivational element for the acquisition of new functional skills, it is understood as relevant to identify how these children consider themselves at different domains and the possible relationship between parenting styles and children's self-assessments. This study aimed to compare the parenting styles of family caregivers, the self-concept and self-efficacy of children with physical disabilities (PD) and children with typical development (TD), and evaluate relations among these self-assessments and parenting styles of their caregivers relatives. In this study 112 participants were grouped as follows: 20 children with PD, boys and girls, aged 8 and 12, from all motor impairment levels (mild, moderate and severe), inserted into regular school setting; 36 children with CP and 56 main family caregivers of children targeted in the study Data collection was carried out in public schools located in Natal, in the state of Rio Grande do Norte, Brazil. The instruments used with the children in both groups were the Self-Perception Profile for Children (SPPC) and Perceived Efficacy and Goal Setting System (PEGS), and among the caregivers of both groups one Characterization Data Sheet for the Caregiver and Family Group, one Characterization Data Sheet of Child and the Parenting Styles Inventory (IEP), and also the Gross Motor Function Classification System (GMFCS) - Family Report Questionnaire, used to classify the motor level only in children with PD along with their caregivers. The data were analyzed from the normative tables of each instrument of descriptive and inferential way, and for the comparative analyzes were used the t-test, chi-square, Fisher's exact test, ANOVA-one way and hoc-LSD post, and the correlation analysis, the Pearson Test. Among the results, there was a significant difference in the comparison of self-efficacy and self-concept in the dimension of 'physical appearance', in which the TD group showed higher average of these selfassessments than the PD group. It was also identified significant correlations between parenting practices and child's self- concept, both in the group of children with CP, as in children with mild PD subgroup, as well as between parenting practices and self-efficacy of children only in the TD group. It is considered that this study contributes adding to the knowledge produced in the area of education and health, allowing an analysis of risk and protective factors to human development, focusing simultaneously on families and their children with physical disabilities. The study brings contributions to direct professional performances that largely consider the development contexts, attention to family caregivers involved and active involvement of children with disabilities in investigations about their children's development process, through self-assessment.